Re-employment, Housing Tenure and Squatter Settlements in Turkey: An Empirical Analysis. Issue 1 (2nd January 2016) - Aydede, Yigit
Abstract: Although the change in the Turkish economy in the last 14 years is historical, the primary question for public and academic circles remains unanswered: why hasn't the growth translated into more and better jobs? This paper intends to develop a better understanding about the dragging structural unemployment by investigating the contribution of a possible labour immobility to the unemployment in Turkey. This is the first study that examines the unemployment duration and its relation to residential mobility, more specifically housing tenure in Turkey. It uses the first and only longitudinal survey, Survey of Income and Living Conditions, which became publicly available in 2011. Unlike in developed countries, homeowners in Turkey are often migrants from rural to urban areas living in semi-illegal dwellings. We use this "squatter" effect to reduce the endogeneity problem in estimations, which indicate that residential immobility has a serious impact on unemployment durations in Turkey.